Catalytic effect of zinc naphthenate on the heavy oil low-temperature oxidation in an air injection process. (2nd May 2016) - Li, Jingjing; Wei, Yutao; Tang, Xiaodong; Liu, Xuandong; Deng, Liuyang
ABSTRACT: Air-assisted steam flooding is a new effective technique for enhanced oil recovery in heavy oil reservoirs. The authors prepared zinc naphthenate as the catalyst in the laboratory and the investigated effects on low-temperature oxidation of heavy oil through the isothermal reactor. The results indicated that zinc naphthenate could accelerate the oxygen consumption rate and facilitate the cleavage reaction in the low-temperature oxidation process. The data shed more light on the mechanisms of low-temperature oxidation reactions of heavy oil and can provide a new way to enhance the recovery of heavy oil reservoir.